2012
DOI: 10.3109/0142159x.2012.714876
|View full text |Cite
|
Sign up to set email alerts
|

Assessing a faculty development workshop in narrative medicine

Abstract: Background: Narrative medicine is increasingly popular in undergraduate medical curricula. Moreover, although faculty are expected to use narrative approaches in teaching, few faculty development learning activities have been described. In addition, data on the impact of faculty development initiatives designed to teach narrative are limited, and there is a paucity of tools to assess their impact. Aims: To assess the impact and outcomes of a faculty development workshop on narrative medicine. Methods: Two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Of the seven evaluations that used a pre-post design, six did a pre-test and immediate post-test, and one did a pre-test and long-term post-test (1 year) 22 70. One evaluation used a randomised step-wedge design in which participants were randomised into two groups, and the groups participated in the programme at different times 41 42. Post-tests of programme participants were compared with pre-tests of those who had not yet participated in the programme.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the seven evaluations that used a pre-post design, six did a pre-test and immediate post-test, and one did a pre-test and long-term post-test (1 year) 22 70. One evaluation used a randomised step-wedge design in which participants were randomised into two groups, and the groups participated in the programme at different times 41 42. Post-tests of programme participants were compared with pre-tests of those who had not yet participated in the programme.…”
Section: Resultsmentioning
confidence: 99%
“…Of qualitative programmes deemed as well described, 10 reported high satisfaction,41 42 44 45 51 52 58 69 71 72 84 85 91 while positive impacts were reported on: relationship-building (n=15),15 37 39 40 43–46 49 52 65 73 74 77 81 85 90 empathy (n=10),15 46 49 55 64 73 74 76 77 81 90 perspective-taking/reflection (n=10),37 39 40 43 52 64 73 76 77 84 85 resilience and burnout detection/mitigation (n=4),39 50 81 90 narrative competence (n=3),41 42 44 45 49 confidence/personal accomplishment (n=3),33 40 74 ethical inquiry (n=2),49 64 relevance to work (n=1),33 pedagogical skills (n=1),37 cultural competence (n=1),15 46 and institutional impact (n=1) 37…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable number of studies also assessed the modification of knowledge or skills as a direct result of the narrative medicine intervention (level 2b; N ¼ 14). Liben (2012) reported that faculty participants in a narrative medicine workshop demonstrated the acquisition of narrative terms in a follow-up test and later applied these narrative skills in teaching and clinical settings. Similarly, Ross (2014) recorded significant improvement in a narrative skills assessment administered before and after the completion of a narrative medicine course (mean scores 51.6-71.5, p < 0.001).…”
Section: Level One: Participationmentioning
confidence: 99%
“…Engaging in the process of guided reflection on students’ reflective narratives can facilitate faculty's capacity to serve as reflective role models through an intersubjective process of transformative growth17 since “the student is no longer the person who wrote the reflective narrative, neither is the teacher who responded to it” 39. With regard to professional development, medical education faculty workshop participants have recognised the value of reflective writing as a vehicle for learning about their teaching practice and development,53 and a faculty development workshop on narrative medicine for reflecting on the use of narrative in professional practice has had measureable impacts 54. Recently, a faculty development programme using guided reflective writing promoted reflection and empathy among practicing physicians55 and the integration of written narratives (on meaningful clinical experiences) for reflection within a continuing education programme on mindful communication for primary care physicians helped cultivate intrapersonal and interpersonal mindfulness and improve their sense of well-being 56…”
Section: Introductionmentioning
confidence: 99%